The aeromedical physician assistant. Issue 12 (December 2016) - Radi, Joshua; Brisson, Michael; Line, Michael
Abstract : ABSTRACT: The US Army aeromedical physician assistant (PA) serves aviation units in regards to crewmember medical readiness. All PAs are graduates of a 6-week flight surgeon course. They are responsible for conducting nearly 40% of the annual US Army flight physicals. This unique training and deployment illustrates the growing adaptability of PAs to assume a greater role in military medicine.